2017
DOI: 10.1021/acsami.7b13100
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanocluster-Mediated Cellular Death under Electromagnetic Radiation

Abstract: Gold nanoclusters (Au NCs) have become a promising nanomaterial for cancer therapy because of their biocompatibility and fluorescent properties. In this study, the effect of ultrasmall protein-stabilized 2 nm Au NCs on six types of mammalian cells (fibroblasts, B-lymphocytes, glioblastoma, neuroblastoma, and two types of prostate cancer cells) under electromagnetic radiation is investigated. Cellular association of Au NCs in vitro is concentration-dependent, and Au NCs have low intrinsic toxicity. However, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“… 86 Besides that, Cifuentes-Rius et al found that BSA-AuNCs can also be applied in electromagnetic radiation therapy. 87 Upon 8 min light activation with 15 W microwaves (1 GHz electromagnetic fields), cell viability decreased in six types of mammalian cell lines. At a gold concentration of 50 μg/mL, approximately 50% of the B-lymphocytes, 68% of prostate cancer cells, and 28% of neuroblastoma cells died via induction of apoptosis and necrosis.…”
Section: Auncs As a Tool In Therapymentioning
confidence: 99%
“… 86 Besides that, Cifuentes-Rius et al found that BSA-AuNCs can also be applied in electromagnetic radiation therapy. 87 Upon 8 min light activation with 15 W microwaves (1 GHz electromagnetic fields), cell viability decreased in six types of mammalian cell lines. At a gold concentration of 50 μg/mL, approximately 50% of the B-lymphocytes, 68% of prostate cancer cells, and 28% of neuroblastoma cells died via induction of apoptosis and necrosis.…”
Section: Auncs As a Tool In Therapymentioning
confidence: 99%
“…Through all these approaches, several metal NCs have shown attractive potential in chemotherapy, phototherapy (PTT and PDT), and radiotherapy. Recently, nanocomposites based on metal NCs have also been designed and used in electromagnetic [235] and microwave radiation, [236] thus extending the application spectrum of metal NCs in targeted therapeutics.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…[ 103 ] AuNCs are ultrasmall monodispersed particles (<2 nm in diameter) and differ in characteristics compared to AuNPs in terms of stability, electronic and optical properties ( Figure A,B). [ 104 ] In a patient‐derived xenograft (PDX) model of pancreatic cancer (Figure 5C), Lei et al. found that AuNCs‐siRNA targeting NGF reduced tumor weight, volume and metastasis when compared to relevant controls, with no change in overall body weight (Figure 5D).…”
Section: Preclinical Success Of Nanoparticles For Sirna Deliverymentioning
confidence: 99%